Bone Marrow derived Cell Therapy in Critical Limb Ischemia: A Meta-analysis of Randomized Placebo Controlled Trials. Issue 6 (December 2015) - Peeters Weem, S.M.O.; Teraa, M.; de Borst, G.J.; Verhaar, M.C.; Moll, F.L.
Abstract : Objective/Background: Critical limb ischemia (CLI) is the most advanced stage of peripheral artery disease (PAD), and many patients with CLI are not eligible for conventional revascularization. In the last decade, cell based therapies have been explored as an alternative treatment option for CLI. A meta-analysis was conducted of randomized placebo controlled trials investigating bone marrow (BM) derived cell therapy in patients with CLI. Methods: The MEDLINE, Embase, and the Cochrane Controlled Trials Register databases were systematically searched, and all included studies were critically appraised by two independent reviewers. The meta-analysis was performed using a random effects model. Results: Ten studies, totaling 499 patients, were included in this meta-analysis. No significant differences were observed in major amputation rates (relative risk [RR] 0.91; 95% confidence interval [CI] 0.65–1.27), survival (RR 1.00; 95% CI 0.95–1.06), and amputation free survival (RR 1.03; 95% CI 0.86–1.23) between the cell treated and placebo treated patients. The ankle brachial index (mean difference 0.11; 95% CI 0.07–0.16), transcutaneous oxygen measurements (mean difference 11.88; 95% CI 2.73–21.02), and pain score (mean difference –0.72; 95% CI –1.37 to –0.07) were significantly better in the treatment group than in the placebo group. Conclusions: This meta-analysis of placebo controlled trials showed no advantage of stem cell therapy on the primary outcome measures of amputation, survival, and amputation free survival in patients with CLI. The potential benefit of more sophisticated cell based strategies should be explored in future randomized placebo controlled trials.